Analysis of Factors that Affect the Success of E-Learning Implementation of STMIK BI Balikpapan - Surmiati, Surmiati; Hadisaputro, Elvin Leander; Utamajaya, Joy Nashar (Universitas Trilogi, 2021)
E-learning in higher education is a technique to improve learning and teaching experience, and as a tool to educate students through digital media, with or without the guidance of their instructors. STMIK BI Balikpapan has been using it since 2015, but its implementation has not been as optimal as expected. The research aims to identify the factors that influence the success of the application of e-learning in STMIK BI Balikpapan by referring to the model adopted from TAM (Technology Acceptance Model) and TOE (technological, organizational and environment). The research respondents were 94 people. Data were collected through questionnaires and analyzed using the Structural Equation Model (SEM) through the Smart PLS program. The results showed that of the four hypotheses tested, one hypotheses had significant influence (habits) and the other three hypotheses were not significant (connections, motivation and facility).